An Analysis of Socio-environmental Resistance in México - Almazán Aboytes, Javier (Southern perspective / Perspectiva austral, 2024)
Introduction: The article analyzed socio-environmental resistances as a mechanism of struggle employed by communities and territories to defend themselves from external agents threatening their environment. It highlighted the opposition between a communitarian vision of the environment and the capitalist logic of exploitation, evidencing the constant repression and violence exercised against those who defend their territory.Development: From the perspective of political ecology, a perspective was presented that made it possible to understand socio-environmental resistance not only as a reaction, but as an articulated strategy in defense of life. It was emphasized that the struggle should not be limited to a theory, but should be translated into concrete actions that guarantee the continuity of resistance. It was mentioned that the climate and social crisis represented imminent threats to humanity, and that ignoring them would mean accepting environmental and social devastationConclusions: The article concluded that vindicating and replicating socio-environmental struggles was fundamental for the protection of the planet and communities. A call was made to not forget those who sacrificed their lives for the cause, highlighting the importance of continuing the battle in different contexts. Resistance was presented as an act of hope and a commitment to the future of humanity.